Culture and characterization of Microcystis spp. and their effects on cladoceran population growth - Shakri, Adibah (2018)
Toxic cyanobacterial species such as Microcystis spp. can form harmful blooms that cause water quality deterioration and negatively impact aquatic life in addition to triggering health risks towards human. This study aimed to isolate Microcystis spp. that produce a toxin, microcystin, and assess their impacts on the growth and reproductive capacity of a cladoceran zooplankton which feeds on microalgae as its main diet. Two Microcystis spp. were isolated and identified with both conventional and molecular methods. Species and toxicity identification for both species were done by using polymerase chain reaction (PCR) with the use of 16S rRNA and mcyB gene sequence. Apart from molecular approach, nuclear magnetic resonance (NMR) was used to detect the presence of microcystin in both isolates. Samples were obtained during the exponential phase, freeze dried and kept in -80˚C freezer prior to toxin extraction. Lyophilized cells were extracted using 75% methanol and dried in vacuo at 40˚C. Each sample was transferred to 1.5 ml amber vial before analysis. 10% of both Microcystis culture (at exponential phase) was transferred into the culture medium with limited nutrient availability (25% reduction = N75 and P75; 50% reduction = N50 and P50; 75% reduction = N25 and P25 from initial concentration (15g L-1). Growth was determined by cell density, optical density and dry weight measurements. Moina micrura was used in population growth study and chronic bioassays. For the population growth study, M. micrura was exposed to three different species of microalgae; Microcystis aeruginosa, Microcystis viridis, and Chlorella vulgaris as a control. For chronic bioassay, 20 neonates (< 24h) were individually reared in glass vials. All the glass vials were checked daily (at 12h intervals) to determine age at first reproduction (day), fecundity (no of eggs female-1), total offsprings (no. of offsprings female-1) and longevity (no. of days). The chronic bioassays were terminated when all the cladocerans died (13 days). Based on 16S rRNA and mcyB genes sequences, two potential microcystin producer Microcystis spp. were successfully isolated, purified and identified as Microcystis aeruginosa (UPMC-A0038, GenBank ID number KX447651.1) and Microcystis viridis (UPMC-A0039, GenBank ID number KY009735.1). Both isolates varied substantially in terms of morphological features such as cell size, colonial formation and cell arrangement. In addition, 1H NMR results showed the presence of Adda group had confirmed microcystin in both Microcystis species. Both Microcystis spp. growth decreased under low nutrient concentrations. Nitrogen and phosphorus play an equal roles in the growth of Microcystis. Compared to M. aeruginosa, the growth of M. viridis was severely affected under low phosphorus level. In addition, M. viridis responded differently toward nitrogen limitation and exhibited adaptive mechanism in low nutrient environment. Both Microcystis spp. were toxic to M. micrura. The mortality rates of M. micrura subjected to M. aeruginosa and M. viridis were significantly higher (p<0.05) than the control treatment. Moina micrura exposed to M. aeruginosa did not reach maturity as their mean body size only reached 627.80±31.4 μm compared to M. micrura fed with C. vulgaris (814.94 ±21.84 μm) and M. viridis (914.21±12.64 μm). The population growth rate of M. micrura fed with C. vulgaris was 0.28 day-1 while growth rates were negative when fed with M. aeruginosa (-0.23 day-1) and M. viridis (-0.20 day-1). Longer exposure of M. micrura to M. aeruginosa resulted in delayed production of M. micrura’s first offspring, which only occurred on day 6 compared to M. micrura fed with C. vulgaris which produced their first offspring on day 3. In conclusion, both Microcystis spp. were microcystin producer species and nutrients play an important role in promoting Microcystis growth. This study also indicated that toxicity of both Microcystis spp. negatively affected M. micrura growth, survival as well as their reproductive capacity.